The Effectiveness of Interactive Activity-Based Coding Instruction on Elementary School Students’ Digital Literacy and Critical Thinking Skills: An Experimental Study - Restu Kurniasari; Lilik Sri Hariani; Endang Surjati (Didaktika: Jurnal Kependidikan, 2026)
This study aims to analyze the effect of coding instruction on improving digital literacy and critical thinking skills among elementary school students. The background of this study is based on the low levels of students’ digital literacy and critical thinking skills, as well as the need for learning approaches that can develop 21st-century competencies in a contextual and meaningful manner. This study employed a quasi-experimental approach using a pretest–posttest control group design. The research subjects consisted of two groups: an experimental group that received interactive activity-based coding instruction and a control group that received conventional instruction. The research instruments included a digital literacy test and a critical thinking test, both of which had undergone validity and reliability testing. Data analysis was conducted using normality tests, homogeneity tests, independent samples t-tests, paired samples t-tests, N-Gain analysis, and effect size calculations (Cohen’s d). The results showed a significant difference between the experimental and control groups in posttest scores for digital literacy and critical thinking skills. The improvement in students’ abilities in the experimental group was categorized as moderate based on N-Gain values, while the control group showed low improvement. In addition, the effect size indicated a very large impact of coding instruction on students’ digital literacy and critical thinking skills. These findings demonstrate that coding instruction is effective in enhancing elementary school students’ digital literacy and critical thinking skills and can serve as an alternative learning strategy to support the development of 21st-century competencies in primary education.